Money-financed fiscal stimulus: The effects of implementation lag - Takayuki Tsuruga; Shota Wake (Osaka University, Institute of Social and Economic Research (ISER), 2018)
Previous studies argue that, based on the New Keynesian framework, a fiscal stimulus financed by money creation has a strong positive effect on output under a reasonable degree of nominal price rigidities. This paper investigates the effects of implementation lag in the moneyfinanced fiscal stimulus on output. We show that if a money-financed government purchase has a time lag between the decision and the implementation: (1) it may cause a recession rather than a boom when the economy is in normal times; (2) it may deepen a recession when the economy is caught in a liquidity trap; (3) the longer is the implementation lag, the deeper is the recession; and (4) the depth of the recession depends on the interest semi-elasticity of money demand. Our results imply that to strengthen the efficacy of the money-financed fiscal stimulus, policymakers should shorten the implementation lag based on detailed knowledge of the money demand function.
Keywords: E32; E52; E62; 330; Anticipation effect; Fiscal multiplier; Government spending; Seigniorage